2019
DOI: 10.3390/ijms20122943
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Glutamatergic Neurotransmission and Brain-Derived Neurotrophic Factor in the Regulation of Behaviors after Nicotine Administration

Abstract: Nicotine causes tobacco dependence, which may result in fatal respiratory diseases. The striatum is a key structure of forebrain basal nuclei associated with nicotine dependence. In the striatum, glutamate release is increased when α7 nicotinic acetylcholine receptors expressed in the glutamatergic terminals are exposed to nicotine, and over-stimulates glutamate receptors in gamma amino-butyric acid (GABA)ergic neurons. These receptor over-stimulations in turn potentiate GABAergic outputs to forebrain basal nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Most other studies found serotonergic or dopaminergic signaling to be involved in FP [18] and we recently re- based on genomic studies in the very same population as used in the current study [21,25]. Cholinergic signaling has not been implicated in FP so far, but is linked to both monoamine as well as GABAergic signaling and is implicated in certain psychiatric disorders [33]. In particular, α7 nAChRs have a crucial role in the dysfunction of cortical parvalbumin-positive GABAergic neurons, as seen in schizophrenia [34].…”
Section: Discussionmentioning
confidence: 78%
“…Most other studies found serotonergic or dopaminergic signaling to be involved in FP [18] and we recently re- based on genomic studies in the very same population as used in the current study [21,25]. Cholinergic signaling has not been implicated in FP so far, but is linked to both monoamine as well as GABAergic signaling and is implicated in certain psychiatric disorders [33]. In particular, α7 nAChRs have a crucial role in the dysfunction of cortical parvalbumin-positive GABAergic neurons, as seen in schizophrenia [34].…”
Section: Discussionmentioning
confidence: 78%
“…The BDNF expression is closely related to a7nAChRs (J. Kim et al, 2019;Moriguchi et al, 2020). Blocking a7nAChRs reduces the BDNF expression in the hippocampus (Freedman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Excitatory inputs from N-methyl-D-aspartate (NMDA) receptors in the VTA increase dopamine levels in the NAcc via activation of presynaptic nAChRs on glutamatergic terminals. Nicotine-induced dopamine levels are also modulated by inhibitory GABA-ergic input including GABA-ergic inhibitory afferents to VTA dopaminergic receptors, inhibitory GABA-ergic interneurons within the VTA and inhibitory medium spiny neurons in the NAcc (Kim et al 2019, Watkins, Koob, and Markou 2000, D’Souza and Markou 2013, Wills et al 2022, Pistillo et al 2015).…”
Section: Introductionmentioning
confidence: 99%